2021
DOI: 10.3390/ijms222111378
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Natural Killer Cell Dysfunction: The Prime Suspect in the Case of Metastasis Following Curative Cancer Surgery

Abstract: Surgical resection is the foundation for the curative treatment of solid tumors. However, metastatic recurrence due to the difficulty in eradicating micrometastases remain a feared outcome. Paradoxically, despite the beneficial effects of surgical removal of the primary tumor, the physiological stress resulting from surgical trauma serves to promote cancer recurrence and metastasis. The postoperative environment suppresses critical anti-tumor immune effector cells, including Natural Killer (NK) cells. The lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 301 publications
(431 reference statements)
0
14
0
Order By: Relevance
“…prostaglandin E2); anti‐inflammatory phase factors interleukin‐6 (IL‐6), interleukin‐10 (IL‐10) and transforming growth factor‐β1 (TGF‐β1); regulatory T‐cells; and myeloid‐derived suppressor cells (MDSCs). [2]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…prostaglandin E2); anti‐inflammatory phase factors interleukin‐6 (IL‐6), interleukin‐10 (IL‐10) and transforming growth factor‐β1 (TGF‐β1); regulatory T‐cells; and myeloid‐derived suppressor cells (MDSCs). [2]…”
Section: Discussionmentioning
confidence: 99%
“…prostaglandin E2); anti-inflammatory phase factors interleukin-6 (IL-6), interleukin-10 (IL-10) and transforming growth factor-β1 (TGF-β1); regulatory T-cells; and myeloidderived suppressor cells (MDSCs). [2] In summary, for NK-cell, B-cell and T-cell lymphocytes generally, exhaustion could be defined as an impaired state resulting from antigenic overstimulation, anergy could be defined as an impaired state resulting from inadequate stimulation of the activating receptors, senescence could be defined as an impaired state resulting from the ageing of the lymphocyte, and suppression could be defined as an impaired state resulting from the inhibiting actions of external non-antigenic factors.…”
Section: Lymphocyteexhaustionanergycellular Senescenceandsuppressionmentioning
confidence: 99%
“…High percentages of post-operative peripheral CD3(+), CD4(+), and CD8(+) T cells predict lower recurrence free survival in patients with CRC as they exert anti-tumor functions (65). The postoperative environment suppresses NK cells, which are critical mediators in the formation of metastases immediately following surgery (66). Moreover, it has been shown that absolute monocyte count decrease predicts worse overall survival and disease-free survival in esophageal squamous cell carcinoma undergoing curative resection (67).…”
Section: Discussionmentioning
confidence: 99%
“…These changes in the immune system may result in tumor proliferation, invasion and migration, and they are important factors leading to postoperative tumor recurrence and metastasis. 12–14 Currently, immunotherapy, including immunoadaptive infusion of T lymphocytes 15 and PD-1/PDL-1 inhibitors, 16 has achieved satisfactory results for cancer treatment. Immunosuppression in cancer patients constitutes the second clinical and biological feature of the tumor.…”
Section: Five Clinical and Biological Features Of Tumorsmentioning
confidence: 99%